Distinctive features of attributives in noun phrases in the sentences - Xidirova Nilufar Abdiaxatovna (Peerian Journals Publishing, 2024)
This article investigates the different peculiarities of phrases with the nouns coming with attributive parts of sentences. This units of attributivity are concerning with links with various types of nouns. Taken these phrases with variety of contexts they should be analysed more precisely and clearly, looking into different samples they can be shown certain features of adjectives connecting with noun phrases. They are analysed from the exploiting some examples in the work. This study represents various features of attributive expressions within some examples in accordance with some rules given. The analyse shows the accurate principles of such phrases in the sentences
Keywords: natural word order; inverted word order; attributive expressions